1999
DOI: 10.2190/ub6t-qf51-af5j-mlcd
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of Death Anxiety and Death Depression to Religion and Civilian War-Related Experiences in Iranians

Abstract: Of eleven hundred seventy-six Iranian college students, those who were more exposed to war-related traumatic events and those who were less religious had higher death anxiety and death depression. The specific variables that contributed the most variance to both death anxiety and death depression were weaker religious belief, female gender, injury to friends or relatives, death of friends or relatives, not believing in life after death, and maintaining that the most important aspect of religion is life after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 6 publications
2
33
0
Order By: Relevance
“…This may be because Lithuanians families have experienced more death and fear of horrendous death due to political repression than Americans. This explanation is consistent with the finding that Iranian college students who had experienced greater war-related trauma had higher death anxiety than those with less exposure (Roshdieh, Templer, Cannon, & Canfield, 1998). Lithuanians' greater fear of the dying process may also be related to their greater familiarity with some of the specific external causes of death mentioned in the subscale.…”
Section: Discussionsupporting
confidence: 85%
“…This may be because Lithuanians families have experienced more death and fear of horrendous death due to political repression than Americans. This explanation is consistent with the finding that Iranian college students who had experienced greater war-related trauma had higher death anxiety than those with less exposure (Roshdieh, Templer, Cannon, & Canfield, 1998). Lithuanians' greater fear of the dying process may also be related to their greater familiarity with some of the specific external causes of death mentioned in the subscale.…”
Section: Discussionsupporting
confidence: 85%
“…They found that Hindus (who had the greatest belief in life after death) also tested lowest in death anxiety, followed by the Muslims, while the Christians showed the highest death anxiety. A few years later, Roshdieh, Templer, Cannon, and Canfield (1999) studied death anxiety and death depression among 1,176 Iranian Muslims who had war-related exposure during the Iran-Iraq war. They found that those who scored higher on death anxiety were those who also had weaker religious beliefs, did not believe in life after death, and did not assert that the notion of the existence of life after death was the most important aspect of religion.…”
Section: Death Anxiety: the Fear Of Deathmentioning
confidence: 99%
“…Pargament's religious coping theory (1990; 1996; 1997) suggests that religion helps people cope with adverse events by offering an explanation and helping people to make meaning of the events. In support of Pargament's model, research with Muslim/Middle Eastern participants --including participants who were exposed to war trauma --found that religiosity was related to lower levels of anxiety and depression, suggesting that Islam may act as a buffer to negative life events (Roshdieh, Templer, Cannon, & Canfield, 1999;Suhail & Akram, 2002;Baroun, 2006).…”
Section: Discussion Of Main Resultsmentioning
confidence: 95%
“…Some research using Muslim participant samples has also indicated that high scores on religious commitment, as it relates to both the level of belief and practice, tend to mitigate death distress (e.g., anxiety, depression, and obsession regarding death and one's mortality; Suhail & Akram, 2002). Similarly, Roshdieh, Templer, Cannon, and Canfield (1999) studied 1,717 Iranian Muslim college students exposed to war-related events during the 1980-1988 Iran-Iraq war. Those who were more exposed to war-related traumatic events and those who were less religious, had higher death anxiety and death depression.…”
Section: Religionmentioning
confidence: 99%